Novel rhodanines with anticancer activity: design, synthesis and CoMSIA study. Issue 63 (20th June 2016) - Mandal, Subhankar P.; Mithuna; Garg, Aakriti; Sahetya, Sanjana S.; Nagendra, S. R.; Sripad, H. S.; Manjunath, Mendon Manisha; Sitaram; Soni, Mukesh; Baig, R. Nasir; Kumar, S. Vasanth; Kumar, B. R. Prashantha
Abstract : A library of novel rhodanines are reported for their anticancer activity along with the 3D QSAR. Abstract : Three different series of some novel N -substituted rhodanines were designed for anticancer activity and prepared from the corresponding dithiocarbamates. The synthesized compounds were analyzed by IR, NMR and MASS to confirm their structures. All the titled compounds were found to be of Z configuration based on NMR spectral analysis. All the synthesized rhodanines were screened for in vitro anticancer activity against MCF-7 breast cancer cells at the concentration of 10 μg. The compounds showed moderate to significant cytotoxicity. Amongst them, interestingly, compounds10, 22 and33 with cinnamoyl substitution at the 5 th position of the thiazolidine ring system showed significant activity. Further, we subjected all these compounds to a CoMSIA study to study their 3D quantitative structure activity relationships (3D QSAR). The illustration about the design of novel rhodanines, synthesis, analysis, activity against MCF-7 cells and SAR via CoMSIA study are reported here.